Arabinoxylan in Wheat Is More Responsible Than Cellulose for Promoting Intestinal Barrier Function in Weaned Male Piglets. Issue 1 (5th November 2014) - Chen, Hong; Wang, Wei; Degroote, Jeroen; Possemiers, Sam; Chen, Daiwen; De Smet, Stefaan; Michiels, Joris
Abstract: Background: The effect of dietary fiber on intestinal function primarily has been ascribed to its interaction with intestinal bacteria in the hindgut, whereas changes in intestinal bacteria in the host have been considered to depend on fiber composition. Objectives: The objectives of this study were to determine the contribution of the major fiber components to the health-promoting effects of wheat bran on intestinal mucosal barrier function and to elucidate the involvement of microbiota changes in weaned piglets. Methods: Thirty freshly weaned male piglets were assigned to 5 dietary treatment groups ( n = 6) according to litter and weight. The piglets consumed synthetic diets ad libitum for 30 d, including a basal control diet (CON) without fiber components, a wheat bran diet (WB) as reference diet (10% wheat bran), and 3 other diets containing amounts of fiber components equivalent to those in the WB, i.e., an arabinoxylan diet (AX), a cellulose diet (CEL), and a combined arabinoxylan and cellulose diet (CB). Results: The groups consuming diets containing arabinoxylans (i.e., the WB, AX, and CB groups) had increased intestinal secretory immunoglobulin A concentrations, goblet cell number and cecal short-chain fatty acid concentrations, and reduced branched-chain fatty acid concentrations and pH values compared with the CON group. In the WB group, the stimulated secretion of Cl − was suppressed (60.8% and 47.5% change in short-circuit current caused by theophylline and carbachol, respectively) in the distal small intestine compared with the CON group. The AX and CB groups also had increased intestinal alkaline phosphatase activities and reduced intestinal transcellular permeability (by 77.3% and 67.2%, respectively) compared with the CON group. Meanwhile, in the WB group, cecal Bacteroidetes and Enterobacteriaceae populations were lower, and the growth of Lactobacillus was higher in the AX and CB groups than in the CON group, whereas no positive effect on intestinal barrier function was observed in the CEL group. Conclusion: Arabinoxylan in wheat bran, and not cellulose, is mainly responsible for improving various functional components of the intestinal barrier function and the involvement of microbiota changes.